Formulation development and characterization of quercetin loaded poly caprolactone nanoparticles for tumors - Kashif, Muhammad; Ali, Murad; Bushra; Naz, Saira; Amir, Jalal; Murad, Shafaq; Atif, Muhammad; Khattak, Osama Ali; Ullah, Saif; Aleena, Seeqal; Khan, Naqash; Khan, Muhammad Younis (Brazilian Journal of Science, 2024)
Cancer is a formidable health obstacle, characterized by its bleak outlook. Considerable scientific investigation has shed light on the capacity to modify the dispersion of anticancer medications at various levels within tissues and cells by enclosing them within submicronic colloidal systems, often known as nanoparticles. This approach is based on the goal of enhancing the therapeutic effectiveness of these medications while minimizing adverse effects on the entire body. Moreover, the theragnostic characteristics of these nanoparticles are widely acknowledged, hence enhancing their therapeutic potential. The current study is centered on exploring the potential anti-tumor effects of quercetin by utilizing its antioxidant capabilities. The quercetin nanoparticles are synthesized with great precision utilizing the nanoprecipitation approach, in which poly(caprolactone) is utilized as the polymer matrix. Following synthesis, the nanoparticles are extracted for further analysis. Further attempts are undertaken to enhance the drug loading process, and the resultant nanoparticles undergo a thorough analysis, including the examination of their morphology using scanning electron microscopy, and the evaluation of drug-polymer interactions using Fourier transform infrared spectroscopy and differential scanning calorimetry. The remarkable efficacy of quercetin’s envelopment can be attributed to its lipophilic nature, reaching a maximum of 81%. The utilization of scanning electron microscopy allows for the observation of nanoparticles with varying forms. Conversely, the absence of noticeable interactions in Fourier-transform infrared analysis indicates the stability of poly(caprolactone) nanoparticles loaded with quercetin.